Attitude Towards Family Planning Among Chenchu Tribes Athmakur (M), Kurnool (D), Ap. - M, Harinder.; Ayesha (International Journal of Psychosocial Rehabilitation, 2020)
The tribal population in India is 1210.8 million according to the 2011 census. The health practices of the tribes are still old practices they are not ready for modern practices even though they can avail the facility of the primary health care centres and the community health care centres. The family is a social institution that performs several functions for the development of individuals and society. Family as institution responsible for socialization, reproduction, economic function, and social status. Family planning is important for improving the reproductive health and well-being of tribal women in India. Some of the reasons for this are low education, phobia of adverse health consequences, lack of accessibility and knowledge of contraception1. Family planning can help tribal women to have the desired number and spacing of children, prevent unwanted pregnancies and abortions, and reduce maternal and child mortality. Objectives for the study is to understand the socio economic conditions, to assess the awareness on family planning and attitude of Chenchu tribes at Athmakur Mandal, Kurnool, Andhra Pradesh. According to the primary data, the universal population of the Chenchu tribes in the said area is a total of 85 and the researcher was able to reach and collect data from 70 respondents. The Chenchu tribes are a Dravidian tribe that live in the Nallamala forest of Andhra Pradesh and Telangana. Despite the government’s initiatives, there is still lack of awareness, cultural barriers have direct impact on the attitude of the Chenchu tribes towards family planning. These barriers may include limited choice of methods, limited access to services, fear or experience of side-effects, cultural or religious opposition, poor quality of available services, users’ and providers’ bias against some methods, and gender-based barriers to accessing services6. Therefore, it is important to understand the factors that influence the Chenchu tribes’ decision-making process regarding family planning and address their specific needs and preferences.